The issue of bad taste, between aesthetic judgment and "guilty" pleasures - Mélissa Thériault (Universidade Federal de Santa Catarina, 2017)
In matters of aesthetic appreciation, we all have our "guilty pleasures", those moments when we feel we ought not to appreciate a work judged unworthy of esteem, but when, like it or not, we find it undeniably pleasing. Sometimes termed aesthetic akrasia (a concept taken from the vocabulary of ethics), this common tendency means to act against one's better judgment, that is, to demonstrate irrationality by failing to react in what is supposed to be the correct way (in this instance, by disliking "good" art or liking "bad" art). In line with this perspective, there are good and bad aesthetic judgments. Now, this implies a belief that an objective standard for aesthetic quality exists (not obvious to begin with), and that it is therefore possible to determine whether or not an artefact complies with this standard. What are the grounds for the "ethical command" that maintains we ought to disapprove of what we like for the sake of convention? Is there not something profoundly problematic in the idea that we "ought to" appreciate works based on a heterogeneous standard rather than on how we really feel about them? This purpose of this article is to discuss these issues, which are at once fascinating and polemical.